Algorithms and applications of intelligent swarm cooperative control: A comprehensive survey. (1st November 2022) - Xu, Xiao-ping; Yan, Xiao-ting; Yang, Wen-yuan; An, Kai; Huang, Wei; Wang, Yuan
Abstract: The intelligent swarm concept has attracted much interest in recent years. Intelligent swarms have been deployed in many real-world applications, such as transportations, target tracking, search and rescue. Since most of these applications usually have very complex goals, the cooperative control approaches of intelligent swarms are very important, and the requirements of better utilizations of intelligent swarms make the efficient control of swarms a critical challenge that needs to overcome. This article reviews the profound cooperative control approaches of intelligent swarms, mainly focus on three kinds of typical intelligent swarms, UAV swarm, missile swarm and hypersonic aircraft swarm. The formation control approaches and decision-making approaches are both surveyed, as well as some typical real-world scenarios. Each approach is investigated based on different criteria, which highlights its distinct advantages and disadvantages. Finally, we present some discussions and recommendations for further investigation. Highlights: Cooperative control approaches of intelligent swarms were reviewed. UAV swarm, missile swarm and hypersonic aircraft swarm were evaluated. Formation control approaches and decision-making approaches were both studied. Each approach was investigated based on different criteria, including advantages and disadvantages.